THERMODYNAMIC DESCRIPTION OF CHLORIDE, HYDROSULFIDE, AND HYDROXO COMPLEXES OF AG(I), CU(I), AND AU(I) AT TEMPERATURES OF 25-500°C AND PRESSURES OF 1-2000 BAR - Akinfiev N.N.; Zotov A.V. (My University, 2001)
The available experimental data on the stability constants of chloride, hydrosulfide, and hydroxo complexes of Ag(l), Cu(l), and Au(l) under hydrothermal conditions were processed. ne procedure employed the Helgeson-Kirkham-Flowers (HKF) equation of state and approximate estimates of the model parameters based on the isocoulomb principle and the model of ion associations. The resulting set of the thermodynamic properties of aqueous species allows the evaluation of equilibria in the system Ag(I)-Cu(I)-Au(I)-S(II)-Cl-O-H in a wide range of temperatures (25-500 degreesC) and pressures (1-2000 bar).